KEEPING CREDIBILITY. WHY IT IS IMPORTANT TO REINFORCE EMERGENCY RESPONSE MECHANISMS IN THE DIALOGUE BETWEEN THE IEA AND ITS NEW PRIORITY COOPERATION COUNTRIES - CARTAGENA NÚÑEZ, IGNACIO (Journal of the Spanish Institute for Strategic Studies, 2018)
In October 2013, the International Energy Agency (IEA) launched an enhanced dialogue with a number of non-member states. Some of them are big consumers and some are also producers; all of them are emerging economies, and, as such, they are destined to play a very significant role in the evolution of the Agency in the years to come. This paper argues that, in this context, preserving and reinforcing the IEA emergency response mechanisms is essential. If this aspect is not adequately tackled in the dialogue with new priority cooperation countries, the IEA will lose credibility as an energy security organization. And credibility is a key factor in the energy sector, where actors tend to exert an influence on each other by sending political signals, rather than by implementing political actions.This paper concludes that, in order to preserve the emergency response mechanisms currently in place, a binding protocol should be signed between the IEA and its new priority cooperation countries